A cobertura noticiosa e as rentabilidades anormais extremas das ações das empresas do PSI-20 - Ana Luísa Nogueira Parada Ferreira e Silva (2017)
The information about companies operating in the capital market is not restricted to messages disclosed by companies neither by or trough regulatory authorities. There are other different entities that disclose information. In this context, the media, particularly the economic press, are assumed to be an important source of information, since they publish news about companies and events, as well as are accessible to all audiences. In turn, companies in general and listed companies in particular tend to increasingly use voluntary communication, also as a result of the huge evolution of information technology. For this they use a variety of instruments to disseminate information. On the one hand, this study aims to investigate how and whether the large price changes in the listed companies (extreme abnormal returns) are covered by the media. On the other hand, it considers whether the news show the existence of information management practices by companies. We concluded that large price changes experienced by companies are reported by the newspapers. However, news coverage of great price rises is distinct from that held in situations of great price declines in several aspects, such as: the number of calls to the front page of newspaper, company as an information source and news content. There also are differences concerning information issued by the Information Disclosed System of CMVM. This research also allowed to verify that companies sometimes seem to promote information management, sending information to media in order to try to capitalize the positive impact of positive abnormal returns and to minimize the negative impact of negative abnormal returns.